Detection, identification and protection of third-country national victims of human trafficking in Ireland - Emily Cunniffe; Oluwatoyos Ayodele (The Economic and Social Research Institute (ESRI), 2022)
In Ireland, between 2015 and 2020, 356 people were identified as suspected victims of human trafficking by An Garda Síochána. Of them, approximately 59 per cent were third-country nationals. This study examines the policy and practice in Ireland for the detection of a situation of human trafficking, the identification of a victim of human trafficking, and the subsequent protection provided to victims of human trafficking, with a particular focus on third-country nationals. It is based on the Irish contribution to a European Migration Network (EMN) report comparing the situation in EMN Member and Observer States.
Keywords: 330; Menschenhandel; Soziale Sicherheit; Irland